Analisis Pelayanan Prima Instansi Pemerintah Studi: Kantor Camat Lhoksukon Kabupaten Aceh Utara - Irfan, M; Fithra, Herman; Hafni, Nur (Program Magister Administrasi Publik, 2023)
The Lhoksukon sub-district office is a government agency that provides services to the community. Good service must be supported by professional, responsible, and competent employees, able to understand and carry out their main duties and functions in accordance with the given field. - Move in and take care of letters of recommendation. The reason is that some people who take care of incoming and outgoing letters of recommendation complain that they have to wait a few days to get a letter at the Lhokukon sub-district office. The approach used by the author in this study uses a descriptive qualitative research approach. The first step in optimizing public services at the Lhoksukon District Office is to utilize technology, namely the use of social media as a forum for managing incoming and outgoing letters and letters of recommendation. This is intended so that the services provided by the apparatus are maximized and can reduce management time to be faster, moreover the costs needed by the community will be more efficient, one of which is the cost of looting transportation between villages and community homes to the Lhoksukon Sub-District Office, North Aceh Regency. Barriers to the implementation of public services in Lhoksukon District, among others, residents do not understand population administration, lack of village employees, low Human Resources (HR), lack of adequate facilities and infrastructure, lack of electronic devices, because of public service standards.